Women with a Preterm Cesarean Have High Rates of Successful Trial of Labor in a Subsequent Term Pregnancy - Rietveld, Anna L.; Heestermans, Lotte A. P. H.; Kazemier, Brenda M.; Teunissen, Pim W.; de Groot, Christianne J. M. (American Journal of Perinatology, 2019)
Objective The rate of cesareans has increased worldwide. Therefore, an increasing number of women has to decide how to deliver in a subsequent pregnancy. Individualized information on risks and success chances is helpful. This study investigates the effect of a preterm cesarean on success of subsequent term trial of labor.Study Design Ten-year Dutch cohort (2000–2009) of women with one previous cesarean and a subsequent term trial of labor. Subgroups were made based on gestational age at first cesarean delivery (25–28, 28–30, 30–32 and 32–34 weeks) and stratified based the way in which second delivery started. Rates of vaginal deliveries, maternal, and neonatal outcomes were compared with women who had a first-term cesarean (37–43 weeks).Results Four thousand three-hundred forty-two women delivered by preterm cesarean in the first pregnancy. These women had high rates of successful trial of labor, both after spontaneous onset (86.2–96.2%) and induction (72.8–75.4%). Rates of adverse outcomes were low and similar compared with women with a previous term cesarean.Conclusion In this 10-year nationwide cohort, women with a preterm first cesarean who opted for trial of labor in a subsequent pregnancy had high rates of successful trial of labor.
Keywords: cesarean delivery; trial of labor; vaginal birth after cesarean; preterm cesarean